Identification of Alcohol-Dependence Biomarkers in plasma by using Metabolomics Analysis - Mostafa, Hamza Mohamed Amin; Mostafa, Arwa Mohamed Amin; Arif, Nor Hayati; Chin, Hoe Teh; Ibrahim, Baharudin (2014)
The main clinical methods to diagnose Alcohol-dependence (AD) in clinical practice currently depend on AD assessment questionnaires and some biomarkers such as Carbohydrate-Deficient Transferrin (CDT), Gamma Glutamyl Transferase (GGT) and Phosphatidylethanol (PEth). These two methods have been shown to have lack of specificity and sensitivity. Metabolomics technique by using nuclear magnetic resonance spectroscopy (NMR) of plasma can help us to identify novel biomarkers which could help in the more accurate diagnosis of AD.